A cross-sectional survey of the prevalence of environmental tobacco smoke preventive care provision by child health services in Australia - Daly Justine B; Heard Todd R; Bowman Jennifer A; Freund Megan AG; Wiggers John H (BMC, 2011)
Abstract Background Despite the need for a reduction in levels of childhood exposure to environmental tobacco smoke (ETS) being a recognised public health goal, the delivery of ETS preventive care in child health service settings remains a largely unstudied area. The purpose of this study was to determine the prevalence of ETS preventive care in child health services; differences in the provision of care by type of service; the prevalence of strategies to support such care; and the association between care support strategies and care provision. Method One-hundred and fifty-one (83%) child health service managers within New South Wales, Australia completed a questionnaire in 2002 regarding the: assessment of parental smoking and child ETS exposure; the provision of parental smoking cessation and ETS-exposure reduction advice; and strategies used to support the provision of such care. Child health services were categorised based on their size and case-mix, and a chi-square analysis was performed to compare the prevalence of ETS risk assessment and ETS prevention advice between service types. Logistic regression analysis was used to examine associations between the existence of care support strategies and the provision of ETS risk assessment and ETS exposure prevention advice. Results A significant proportion of services reported that they did not assess parental smoking status (26%), and reported that they did not assess the ETS exposure (78%) of any child. Forty four percent of services reported that they did not provide smoking cessation advice and 20% reported they did not provide ETS exposure prevention advice. Community based child and family health services reported a greater prevalence of ETS preventive care compared to other hospital based units. Less than half of the services reported having strategies to support the provision of ETS preventive care. The existence of such support strategies was associated with greater odds of care provision. Conclusions The existence of major gaps in recommended ETS preventive care provision suggests a need for additional initiatives to increase such care delivery. The low prevalence of strategies that support such care delivery suggests a potential avenue to achieve this outcome.